Evidence for vortex splitting at the grain boundary in long YBa2Cu3O7−δ grain boundary junctions. (17th July 2018) - Hua, Tao; Yu, Mei; Geng, Haifeng; Xu, Weiwei; Lu, Yapeng; Shi, Jianxin; Shen, Weikang; Wu, Jingbo; Wang, Huabing; Chen, Jian; Wu, Peiheng
Abstract: We investigated the current–voltage characteristics and the critical current density ( J c ) of a YBa2 Cu3 O7− δ grain boundary (GB) long Josephson junction with respect to magnetic field ( H ) under different application directions. When H is rotated within the bc -plane of the film, a small peak of J c is observed when H is parallel to the c -axis, which denotes that there are some residual c -axis dislocations in the GB. When H is rotated within the ac -plane, some vortex-flow steps can be observed in the current–voltage curve at a high inclination angle of H . The vortex-flow step becomes smaller and wider with the decreasing angle between H and the c -axis. These results are a clear demonstration of vortex splitting at the GB plane in YBa2 Cu3 O7− δ GB long Josephson junctions.